Age of First Arrest, Sex, and Drug Use as Correlates of Adult Risk Behaviors Among Rural Women in Jails - Staton, Michele (2017)
Incarcerated women frequently report initiation of substance use and sexual encounters at an early age, and often engage in high-risk drug use and sexual behaviors as adults. This study examined the timing of first sex, drug use, and arrest, as well as their unique influences on specific risky behaviors in adulthood, among a high-risk population of rural women recruited from jails. Ages of initiation were all positively and significantly correlated, and each independently increased the likelihood of several risky behaviors in adulthood. Implications are discussed for screening, intervention, and treatment targeting high-risk women and girls in rural areas, particularly within criminal justice settings